2022
DOI: 10.1186/s11658-022-00346-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of tRNA-derived small RNAs in proliferative human aortic smooth muscle cells

Abstract: Background Abnormal proliferation of vascular smooth muscle cells (VSMCs) contributes to vascular remodeling diseases. Recently, it has been discovered that tRNA-derived small RNAs (tsRNAs), a new type of noncoding RNAs, are related to the proliferation and migration of VSMCs. tsRNAs regulate target gene expression through miRNA-like functions. This study aims to explore the potential of tsRNAs in human aortic smooth muscle cell (HASMC) proliferation. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…tsRNAs have been identified as biomarkers or potential therapeutic targets in many cardiovascular diseases, including rheumatic heart disease [ 40 ], cardiac hypertrophy [ 13 ], heart failure [ 16 ], atherosclerosis [ 41 ], and aortic dissection [ 42 ]. There is evidence that tsRNAs regulate the proliferation [ 43 ] and phenotypic switching [ 44 ] of VSMCs. In our previous work, we also found that tRF-Gln-CTG induced vascular intimal hyperplasia by inhibiting FAS cell surface death receptors [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…tsRNAs have been identified as biomarkers or potential therapeutic targets in many cardiovascular diseases, including rheumatic heart disease [ 40 ], cardiac hypertrophy [ 13 ], heart failure [ 16 ], atherosclerosis [ 41 ], and aortic dissection [ 42 ]. There is evidence that tsRNAs regulate the proliferation [ 43 ] and phenotypic switching [ 44 ] of VSMCs. In our previous work, we also found that tRF-Gln-CTG induced vascular intimal hyperplasia by inhibiting FAS cell surface death receptors [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, with the application of high-throughput sequencing and advances in bioinformatics techniques, an increasing number of tsRNAs in EVs have been reported to be associated with different diseases 28 . The regulatory mechanisms of tsRNAs identi ed so far are diverse: (1) they regulate mRNA stability, similar to miRNAs; (2) they inhibit the initiation and extension of translation; (3) they regulate ribosome biogenesis; and (4) they function as a novel type of epigenetic factor that alter the spatial conformation of proteins and thus affect their functions, such as DNA methylation, histone modi cation, and chromatin remodeling 29 . In various diseases, different tsRNAs have been implicated in regulatory roles.…”
Section: Discussionmentioning
confidence: 99%
“…These complexes are then transported to the nucleus, enhancing the interaction between EEF1A1 and the MDM2 proto-oncogene (MDM2), ultimately promoting GC progression [49]. Additionally, Zhao et al [50] found that the upregulated tRF-Tyr in laryngeal squamous cell carcinoma enhances tumor progression by binding with lactate dehydrogenase A (LDHA), affecting its phosphorylation and leading to increased lactic acid accumulation [50]. These studies highlight the diverse biological roles of tsRNAs, which involve direct binding to target proteins, formation of complexes for intracellular transport, and regulation of posttranslational modifications.…”
Section: Biological Roles Of Tsrnasmentioning
confidence: 99%